Fungsi Pembinaan untuk Meningkatkan Mutu Pembelajaran Madrasah di Lingkungan Kementrian Agama Kabupaten Ciamis - Yasiman; Falah, Darul (Jurnal Garasi Buku dan Obrolan Keilmuan, 2023)
The function of coaching teachers according to the Regulation of the Minister of Religion of the Republic of Indonesia No. 2 of 2012 concerning Madrasa Supervisors and Islamic Religious Education Supervisors in Madrasas article 5 paragraph 3d is carried out by madrasa supervisors either directly to teachers or through the Madrasa Head. The regulation describes the coaching carried out to improve the quality of learning in madrasas. Thus, the supervisory coaching function is indispensable. The approach to writing this paper was prepared using a qualitative descriptive approach. This paper contains steps that can be taken by madrasa supervisors to improve the quality of learning in madrasas. The data source used in the preparation of this paper is based on field observations. The data obtained is then reviewed and processed. Data processing is supported by the results of literacy studies. The combination of the two data is then used as the basis for writing the paper. Development steps based on the Regulation of the Minister of Religion of the Republic of Indonesia Number 2 of 2012 include planning, implementing, and learning outcomes of learning activities in madrasas. Level of Success of the Coaching Function Coaching activities are said to be successful if they are as follows. 1) The teacher makes his own lesson plan to be used; 2) Teachers hold varied learning; 3) The teacher carries out an assessment that is in accordance with the objectives and is varied. The steps for implementing the coaching function to improve the quality of madrasa learning within the Ministry of Religion of Ciamis Regency are as follows. 1) Development of learning planning; 2) Development of the learning process; 3) Guidance on the assessment of learning outcomes Author's suggestion There is a need for further research to determine the level of success of the coaching function.